Kajian Hukum Penanganan Tindak Pidana Kecelakaan Lalu Lintas Dengan Pola Manajemen Kepolisian Berdasarkan Undang-Undang RI Nomor 22 Tahun 2009 Tentang Lalu Lintas dan Angkutan Jalan - Emi Sri Utami (Jurnal Media Justitia Nusantara, 2016)
Traffic problems are problems that cause a lot of problems, because it concerns the problem of order and security in society. According Polrestabes Bandung and Jasa Marga of the results of research in the field shows the rate of accidents in the city and throughout Indonesia is quite high. Based on the above, the authors feel compelled to do more research and then examines the problems that subsequently the authors formulate it in the form of a thesis with the title: "Handling of Legal Study of Traffic Accident Crime With Police Management Pattern Based on Law No.. 22 Year 2009 on Traffic and Road Transportation ". Identify a problem in this thesis include: how police management patterns associated with Law No.. 22 of 2009 on the Road Traffic and Transport investigation?, Whether the pattern of police management in the implementation of criminal investigations of traffic accidents has been applied in accordance with the Standard Of Procedures (SOP)? and how the concept of Manajemen Operasi Kepolisian (MOK) is applied in the service area to reduce traffic accidents in the future? The method used in this compiler is to use normative juridical approach while writing specifications in this thesis is a descriptive analysis, the research phase of this research is primary data that is obtained from field research (interviews) and secondary data from the primary legal materials, secondary legal materials and legal materials tertiary. Based on the description and analysis of the problems it is known that the pattern of police management is associated with Law No. 22 of 2009 on the road freight traffic investigation, theinvestigation process, the Indonesian National Police to make a policy through regulation of the Indonesian National Police Chief No. 8 of 2009 on Implementation and principles and human rights standards in the administration of the Indonesian National Police task. Efforts to optimize the roleof the police in the police as a tool of state who served as a state is obliged to respect and uphold human rights. The pattern of police management in the implementation of criminal investigations of traffic accidents in terms of protection of rights of suspects and defendants in the Criminal Code, including the crime of traffic accident. Legal concept of Police Operations Management (MOK) is applied in the service area to reduce traffic accidents in the future include law enforcement tends to be formal-legalistic means everything must be in accordance with legislation. Advice to convey is that there should be changes to the legislation, the implementation process should also be optimal inthe management or conduct of the investigation conducted by law enforcement officers, who will serve as a police investigator should have provisions and the concept of autonomy (freedom given to the police). That is no limit to the types of crimes that may be handled by the level of Police, Polres, Polwil or Polda.